2013
DOI: 10.1097/meg.0b013e328359fe54
|View full text |Cite
|
Sign up to set email alerts
|

Occult hepatitis B infection in Portuguese patients with chronic hepatitis C liver disease

Abstract: Occult HBV infection occurred in a high percentage of patients but was not clinically significant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(44 citation statements)
references
References 34 publications
(72 reference statements)
1
42
0
1
Order By: Relevance
“…In general, HCV coinfection has been considered as one of the main reasons for inducing OBI [31], and prevalences of occult HBV infection have been reported to be significantly higher in HCV chronically coinfected patients as compared to HCV-negative individuals [32, 33]. …”
Section: Discussionmentioning
confidence: 99%
“…In general, HCV coinfection has been considered as one of the main reasons for inducing OBI [31], and prevalences of occult HBV infection have been reported to be significantly higher in HCV chronically coinfected patients as compared to HCV-negative individuals [32, 33]. …”
Section: Discussionmentioning
confidence: 99%
“…The main characteristics of the 34 studies included in the meta-analysis are summarized in Tables 1 and 2; 6 26,29,42,45,51,53 evaluated the prevalence of OBI in subjects without chronic liver disease, 30 5,7,[22][23][24][25][26][27][28][30][31][32][33][34][35][36][37][38][39][40][41][43][44][45][46][47][48][49][50]52 in those with chronic liver disease and 2 26,45 in both. All were cross-sectional studies, but 3 7,46,50 were cohort studies.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The prevalence of OBI detected in liver tissue was reported as 38.8% in 326 Italian patients with chronic HCV infection[18], 57% in 100 Portuguese patients[19], and 15.0% in 167 Japanese patients as determined by nested PCR[13], and 50% in 44 patients with HCV-related advanced cirrhosis in the United States as determined by real-time PCR[20]. …”
Section: Discussionmentioning
confidence: 99%
“…The OBI prevalence in chronic HCV patients was 45.7% (42/92) in Morocco[25] and 20% (18/50) in Iran[26], while none of 100 Portuguese patients showed serum OBI[19]. A retrospective study in Taiwan showed that serum OBI prevalence as determined by nested PCR using 3 sets of primers in patients with chronic HCV infection was 14.8% (31 of 210), which did not differ from that of healthy controls (15%, 15/100), and the prevalence of OBI did not parallel the severity of liver disease (14.5% in chronic hepatitis, 8% in liver cirrhosis, and 22% in HCC)[27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation